Framework based on Gestalt principles to design mobile interfaces for a better user experience - Ripalda, Daniel (2020)
This paper presents the results of the user experience test comparing a real functional application and a high fidelity prototype that used a Framework to design graphic user interfaces on mobile devices. This Framework links Nielsen's heuristics with the principles of perception of Gestalt, offering to developers and usability experts, references to generate and evaluate mockups and prototypes. The constructive and evaluative model of the Framework allows to recognize usability criteria in visual components of the interfaces, during the initial phases of a project that uses agile software development methodologies, reducing the “trial - error” regressions. The experiment allowed obtaining data about satisfaction measures and specific user attitudes regarding the interfaces developed.